Exosome Processing and Characterization Approaches for Research and Technology Development. Issue 15 (25th March 2022) - Lai, James J.; Chau, Zoe L.; Chen, Sheng‐You; Hill, John J.; Korpany, Katalin V.; Liang, Nai‐Wen; Lin, Li‐Han; Lin, Yi‐Hsuan; Liu, Joanne K.; Liu, Yu‐Chung; Lunde, Ruby; Shen, Wei‐Ting
Abstract: Exosomes are extracellular vesicles that share components of their parent cells and are attractive in biotechnology and biomedical research as potential disease biomarkers as well as therapeutic agents. Crucial to realizing this potential is the ability to manufacture high‐quality exosomes; however, unlike biologics such as proteins, exosomes lack standardized Good Manufacturing Practices for their processing and characterization. Furthermore, there is a lack of well‐characterized reference exosome materials to aid in selection of methods for exosome isolation, purification, and analysis. This review informs exosome research and technology development by comparing exosome processing and characterization methods and recommending exosome workflows. This review also provides a detailed introduction to exosomes, including their physical and chemical properties, roles in normal biological processes and in disease progression, and summarizes some of the on‐going clinical trials. Abstract : The capability to manufacture high quality exosomes is essential for fully realizing their potential as disease biomarkers as well as therapeutic agents. This review informs exosome research and technology development by comparing exosome processing and characterization methods and recommending exosome workflows. The figure shows relative yield, purity, and throughput of different exosome isolation techniques.